Assessing The Synergistic Impact Of Quinoa Extract And Hepatoprotective Properties Of Black Seed Oil On Hepatic Health And Oxidative Stress In A Rat Model Of Cirrhosisia - Zidan, Muftah; Santos, Budi; Iswara , Arya (Al Makki Publisher, 2025)
Cirrhosis is a chronic liver disease characterized by progressive fibrosis and loss of liver function, potentially leading to complications such as portal hypertension, hepatic encephalopathy, and hepatocellular carcinoma. This study aims to evaluate the individual and combined effects of quinoa extract and black seed oil on hepatic health and oxidative stress in a rat model of cirrhosis. Quinoa extract, rich in phenolic compounds, and black seed oil, known for its flavonoid content, both exhibit antioxidant and hepatoprotective properties. The findings reveal that while each treatment offers protective effects, the combination therapy demonstrates a synergistic effect, significantly improving liver enzyme levels, oxidative stress markers, and immune responses. These results suggest that the concurrent use of quinoa extract and black seed oil may offer a comprehensive therapeutic strategy for mitigating liver damage and oxidative stress associated with cirrhosis.